2015
DOI: 10.1515/intag-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic properties of lentil seeds

Abstract: A b s t r a c t. Aerodynamic properties of solid materials have long been used to convey and separate seeds and grains during post-harvest operations. The objective of this study was evaluation of the aerodynamic properties of green and red lentil seeds as a function of moisture content from 10 to 25% (w.b.). The results showed that as the moisture content increased from 10 to 25%, the terminal velocity of seeds increased, following a linear relationship, from 6.90 to 9.14 and from 6.37 to 7.67 m s -1 for gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
(12 reference statements)
3
11
0
Order By: Relevance
“…Kural (1995) reported that variation in physical properties of seeds such as mass, sphericity index and projected area, influenced terminal velocity significantly. The similar results was also found among seeds: lentil by Shahbazi et al, (2015), millets by Baryeh (2002), pistachio by Kashaninejad et al, (2006).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Kural (1995) reported that variation in physical properties of seeds such as mass, sphericity index and projected area, influenced terminal velocity significantly. The similar results was also found among seeds: lentil by Shahbazi et al, (2015), millets by Baryeh (2002), pistachio by Kashaninejad et al, (2006).…”
Section: Resultssupporting
confidence: 84%
“…Approximately, a mass increase of 58 % at chickpea seed and of 87 % at dry bean seed caused a 15 % and 24 % increase of terminal velocity, respectively. Shahbazi et al, (2015) found that the terminal velocity occurred an increase of 32% with increasing projection area from 32.94 to 37.22 mm 2 for lentil seeds. Soylu et.…”
Section: Resultsmentioning
confidence: 88%
“…Thus, the polynomial model was picked out as an appropriate model to predict the drag coefficient of maize kernels as a function of moisture content. Similar results were obtained byShahbazi et al (2015) andNalbandi et al (2010). But a linear equation between moisture content and terminal velocity was observed byGupta et al (2007) in sunflower seed andMatouk et al (2008) in canola seed.…”
supporting
confidence: 91%
“…Furthermore, numerous studies have been conducted on the aerodynamic properties of agricultural products. Shahbazi, Valizadeh, Dowlatshah, and Hassanzadeh (2015) investigated the aerodynamic properties of mung bean seeds as a function of seed moisture content. In this study, seeds were split into two groups in their lengths, that is, Group A (less than 4.8 mm) and Group B (more than 4.8 mm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation